PENGARUH GOOD CORPORATE GOVERNANCE, PROFITABILITAS, DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan yang Terdaftar di Jakarta Islamic Index Tahun 2017-2022) - Majid, Ghufron Nurul; Purwanto, Agus (Diponegoro Journal of Accounting, 2024)
This research aims to analyze the influence of good corporate governance, profitability and solvency on company value moderated by corporate social responsibility. Good corporate governance is measured by the proportion of the board of commissioners, profitability is measured by the ROA ratio, solvency is measured by the DER ratio, company value is measured by Tobin's Q, and corporate social responsibility is indicated by CSRi based on the GRI G4 indicator. The population in this research are companies included in the Jakarta Islamic Index from 2017 to 2022. The sampling method used in this research is purposive sampling. The total number of samples in this research was 47 research samples. The data used in this research was obtained from the Bloomberg Data Base, Company Financial Reports, and Company Sustainability Reports. The data in this research was analyzed using the classic assumption test before the data was tested using the multiple regression test and the Moderated Regression Analysis test. The results of this research show that good corporate governance and profitability have a positive effect on company value. Meanwhile, solvency has a negative effect on company value. The results of this research also show that corporate social responsibility is not able to strengthen or moderate the relationship between good corporate governance and profitability on company value, but is able to strengthen the relationship between solvency and company value.